Distributed Graph Algorithms for Multiple Vector Engines of NEC SX-Aurora TSUBASA Systems - Afanasyev, Ilya V.; Voevodin, Vadim V.; Komatsu, Kazuhiko; Kobayashi, Hiroaki (Supercomputing Frontiers and Innovations, 2021)
This paper describes the world-first attempt to develop distributed graph algorithm implementations, aimed for modern NEC SX-Aurora TSUBASA vector systems. Such systems are equipped with up to eight powerful vector engines, which are capable to significantly accelerate graph processsing and simultaneously increase the scale of processed input graphs. This paper describes distributed implementations of three widely-used graph algorithms: Page Rank (PR), Bellman-Ford Single Source Shortest Paths (further referred as SSSP) and Hyperlink-Induced Topic Search (HITS), evaluating their performance and scalability on Aurora 8 system. In this paper we describe graph partitioning strategies, communication strategies, programming models and single-VE optimizations used in these implementations. The developed implementations achieve 40, 6.6 and 1.3 GTEPS performance on PR, SSSP and HITS algorithm on 8 vector engines, at the same time achieving up to 1.5x, 2x and 2.5x acceleration on 2, 4 and 8 vector engines of Aurora 8 systems. Finally, this paper describes an approach to incorporate distributed graph processing support into our previously developed Vector Graph Library (VGL) framework – a novel framework for graph analytics on NEC SX-Aurora TSUBASA architecture.